Investigating the influence of CaO/CaF2 ratios on the synthesis of calcium-alumino-silicate-fluoride-based glass ceramics utilizing recyclable materials - Roslan, Zuraidah; Amin, Khamirul Matori; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Kul, Esra; Loh, Zhi Wei; Zarzali Shah, Aishah; Ahmad Zahudi, Afrina Zulaikha (Springer, 2024)
This research addresses the significant challenges of waste disposal and the need for sustainable production in the ceramics industry by introducing an approach to fabricating calcium-alumino-silicate-fluoride (CASF) based glass ceramics. Using recyclable materials such as waste soda-lime-silicate (SLS) glass and clam shells (CS) as primary precursors, a controlled melt-quenching process was employed to investigate how varying the CaO/CaF2 ratios influences the physical and structural properties of CASF glass ceramics. The waste materials and CASF glass ceramics were analyzed using X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier transforms infrared (FTIR), Scanning electron microscopy (SEM), and Energy dispersive X-ray (EDX) spectroscopy. XRD indicated the crystalline structure in all CASF glass ceramics samples while FTIR spectroscopy detected several linkages, including PO43−, Si-OH, Si-O-Si, CO2, and O-H indicating the development of CASF glass ceramics. SEM analysis showed a non-uniform distribution of particles and EDX analysis, shows the calcium-to-phosphate molar ratio (Ca/P) of CASF glass ceramics. The glass ceramics labeled as G6 possessed better properties, with a minor crystalline phase identified as fluorapatite (Ca5(PO4)3F), which is compatible with the commercial bioglass. These results demonstrate a cost-effective waste-derived bioglass system used in biomedical fields.